Analisis Manajemen Risiko UMKM Jasa Jahit Mimi Taylor - Nurul Laily Oktaviana; Nira Destiani Dewi; Chika Putri Irwanda; Nabila Zulfa Azizah; Alfiana Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study explores various risks faced by Mimi Taylor MSME, a home-based sewing service business that has been operating since 1997. The analyzed risks include market risks, marketing risks, financial risks, operational risks, human resources risks, and legal aspects. The research method employs a descriptive qualitative approach through field observations and direct interviews with the business owner. The study results indicate that operational and marketing risks are the most prominent, particularly those related to delays in order completion, equipment damage, lack of promotion, and dependence on existing customers. Risk matrix analysis is conducted based on ISO 31000 principles, followed by the design of mitigation strategies for each major risk. This study emphasizes the significance of implementing structured risk management to support the sustainability and competitiveness of small-scale sewing service businesses.